2010
DOI: 10.1021/jm1004489
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus Papain-like Novel Protease Inhibitors: Design, Synthesis, Protein−Ligand X-ray Structure and Biological Evaluation

Abstract: The design, synthesis, X-ray crystal structure, molecular modeling, and biological evaluation of a series of new generation SARS-CoV PLpro inhibitors are described. A new lead compound 3 (6577871) was identified via high-throughput screening of a diverse chemical library. Subsequently, we carried out lead optimization and structure-activity studies to provide a series of improved inhibitors that show potent PLpro inhibition and antiviral activity against SARS-CoV infected Vero E6 cells. Interestingly, the (S)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
183
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(187 citation statements)
references
References 27 publications
3
183
0
1
Order By: Relevance
“…Mechanism of inhibition studies revealed that these compounds are mixed-type inhibitors with α values greater than 1, indicating that they bind to an allosteric site other than its catalytic site, but behave as if they are competitive inhibitors 35 . As noted above, these lead inhibitors bind to the flexible BL2 region and induce conformational changes to block substrate access to the catalytic site of the enzyme 27, 28 . There have been no MERS-PLpro inhibitors published to date; we have identified one compound ( 4 ) that inhibits both SARS-PLpro and MERS-PLpro.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanism of inhibition studies revealed that these compounds are mixed-type inhibitors with α values greater than 1, indicating that they bind to an allosteric site other than its catalytic site, but behave as if they are competitive inhibitors 35 . As noted above, these lead inhibitors bind to the flexible BL2 region and induce conformational changes to block substrate access to the catalytic site of the enzyme 27, 28 . There have been no MERS-PLpro inhibitors published to date; we have identified one compound ( 4 ) that inhibits both SARS-PLpro and MERS-PLpro.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Unlike 3CLpro, the development of PLpro inhibitors has been very limited until recently, despite its essential role in SARS viral replication. In addition to our own work, [11] two very different types of PLpro inhibitors have been reported in recent years. First, 6-Mercaptopurine (6MP) and 6-thioguanine (6TG) were identified from compound screening with IC 50 values of 5 – 20 µM.…”
Section: Introductionmentioning
confidence: 85%
“…[11] Inhibitor 1 (GRL-0068S) has shown an inhibitory activity (IC 50 value) of 0.29 µM and antiviral activity (EC 50 ) of 5.2 µM (See Table 1 for inhibitor structures). Inhibitors 2 (GRL-0617S), 3 (GRL-0667S) and 4 (GRL-0737S) have exhibited inhibitory activities of 1.32 µM, 0.64 µM and 1.36 µM, with antiviral activities of 15 µM, 9.1 µM and 9.1 µM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Thus, PLpro so serves as a model for development of drugs against other deubiquitinating enzymes involved in human diseases. 11) Importantly, endogenous deubiquitinating enzymes are now strongly linked to cancer and neurological disease development and in spite of a huge research effort, no deubiquitinating enzyme inhibitors are as yet even in clinical trials. 12) Tribulus terrestris LINN belongs to the family Zygophyllaceae and is distributed in warm regions throughout India and the southern part of China.…”
mentioning
confidence: 99%
“…17) Many synthetic amide derivatives have been prepared as potential PLpro inhibitors, but no natural amide compounds have yet been shown to exhibit PLpro inhibition. 10,11) This encouraged us to search for PLpro inhibitors from T. terrestris because although it is most well known as a source of saponins, it is also known to contain cinnamic amides. 15) In this study, we isolated six SARS-CoV PLpro inhibitors from the fruits of T. terrestris using bioactivity guided fractionation.…”
mentioning
confidence: 99%